Drill Hole Optimization for Augmenting Structural Integrity - Bisht, Neeraj; Gairola, Suvam; Shekhawat, Shivam; Darshan, Deep; Aithani, Nitesh (Journal of Graphic Era University, 2023)
Structures develop cracks during the course of there life resulting in catastrophic failures. This can be reduced by drilling holes near the crack tip. Here the aspect of optimal position and size of the drill hole has been analysed. Additionally the effect of supplementary hole has also been made. Finite element code ANSYS was used for the analysis. To verify the fracture capabilities of ANSYS the results were corroborated using photoelastic techniques. It was observed that reduction in stress intensity factor to a great extent depends upon the position of the stop hole. Also it was observed that as the radius of the crack was increased the stress intensity factor increased. Creating supplementary hole further reduced the stress intensity factor. So it can be concluded that for employing the concept of drill hole its position and size should be accurately determined.